Chasing the thermodynamical noise limit in whispering-gallery-mode resonators for ultrastable laser frequency stabilization - Jinkang Lim (Nature Portfolio, 2017)
High-quality optical resonators have the potential to provide a miniaturized frequency reference for metrology and sensing but they often lack stability. Here, Lim et al. experimentally characterize the stability of whispering-gallery resonators at their fundamental noise limits.